Legal Protection Of Bank Financial Institution Brand Against Username Squatting Through Twitter Accounts Based On The Trademark Law And The Electronic Information And Transaction Law - Rizka Alifia Zahra; Laina Rafianti; Muhamad Amirulloh (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The use of a brand as a Twitter social media account is one way for brand owners to introduce their goods and/or services as well as a guarantee for their quality. The rise of fake Twitter accounts on behalf of the financial institution Bank Mandiri proves that trademark infringement does not only occur conventionally, but also through the scope of cyberspace. Writing this normative law aims to determine the qualifications for the act of using a bank's financial institution brand as a Twitter social media account and to determine what legal action should be taken by Bank Mandiri against those who use its brand without rights and permission. This research is a legal study employing the normative juridical approach method, a type of legal writing that is conducted by examining library data. The study applies a qualitative analysis method, connecting legal principles, norms, and theories to determine legal qualifications and consequences. The results show that using trademarks as social media accounts should be based on principles, including legal certainty, good faith, and neutrality within technology. Civil law measures offer a proportional legal remedy, seeking compensation for economic harm suffered. This study suggests the need for specific regulations to prohibit the registration and use of trademarks as social media accounts in the virtual space. This research contributes to the understanding of trademark protection in cyberspace, and provides legal guidance for financial institutions to address trademark misuse on social media platforms.